Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan PT Kalbe Farma Tbk - Teresia Febrianti Kewa; Sugeng Suroso; Ery Teguh Prasetyo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the partial and simultaneous influence of the independent variables Leadership Style and Organizational Culture on the dependent variable Employee Performance at PT. Kalbe Farma Tbk. This research was conducted at PT. Kalbe Farma Tbk which is located on Jl. Rawa Gelam IV No. 6m Pulogadung – East Jakarta. This type of research uses a quantitative approach. The population in this study were employees of PT Kalbe Farma Dept. Global supply chain Rawa Gelam. This research uses a purposive sampling technique using a questionnaire distributed to respondents with a total of 80 samples, then the data results are processed using the SPSS 26 data processing application. The results of this research show that in the partial t test, the Leadership Style variable has no significant effect on Employee Performance and Organizational Culture has a significant effect on Employee Performance. The results of the f test show that the Leadership Style and Organizational Culture variables together or simultaneously influence PT Employee Performance. Kalbe Farma Tbk on Jl. Rawa Gelam IV, Pulogadung - East Jakarta.